IMPLEMENTASI SISTEM PEMANTAUAN JARINGAN MENGGUNAKAN LIBRENMS PADA JARINGAN KAMPUS UNIVERSITAS UDAYANA - I Wayan Krisna Saputra; Dewa Made Wiharta; Nyoman Putra Sastra (Program Studi Teknik Elektro UNUD, 2020)
Udayana University is education institutions that has implemented an online learningsystem. The system requires fast and reliable access to internet so students can access themefficiently. In order to meet the need for internet access, it requires to provide infrastructure thatis able to keep internet services running smoothly. Network Monitoring requires an applicationcalled Network Monitoring System. There are many network monitoring applications availablefor free, which provides many option for network operators to carry out monitoring functions.LibreNMS is a popular application because LibreNMS has many features, such as: autodiscovering,flexible and diverse alerting system, comfortable user interface with a dashboardthat can be adjusted to user needs and has wide community support. LibreNMS allows networkadministrators to monitor performance on the network so that it is always available. This studyaims to build a network monitoring system on the Sudirman Campus of Udayana Universityusing LibreNMS. The test results show that LibreNMS is able to display traffic conditions andresource usage on every network device that is monitored.